ロスカイ デノ ソコビキアミ サイシュウ ギョ ニ ツイテ - 岩見, 哲夫; イワミ, テツオ; 阿部, 宗明; アベ, トキハル; Iwami, Tetsuo; Abe, Tokiharu (1981)
P(論文) 南極大陸周辺の魚類相に関する報告は, いくつか行われており, ロス海についても報告されている(ANDRIASHEV, Issled. Fauny Morey, 2(10), 335,1964; DEWITT, Antarct. Map Folio Ser., 15,Am. Geogr. Soc., 10p, 1971; RESECK, N. Z. J. Sci., 4(1), 107,1961). 今回, 海洋水産資源開発センターがロス海において行った底引トロールの試験操業において, 約300個体, 24種の底魚が採捕されたので報告する。個体数としては, Pleuragramma antarcticum BOULENGERが最も多く, 200個体以上, 次いでChionodraco myersi DEWITT and TYLERの51個体であった。採集物を調べた結果, Bathydraco科のVomeridens infuscipinnis(DEWITT)が2個体含まれていたが, この種のロス海よりの報告は, 本報告が最初である。また, Chionodraco myersiの第1背鰭の最長鰭条長に, 性的二型らしき様相が認められたが, 生殖巣の保存状態が悪いため, 確認はできなかった。さらにCryodraco属9個体が含まれていたが, 調べた結果従来のこの属における種の査定には混乱があるように思われた。今回の標本により, 臀鰭基部に沿って縦走する側線について, 二型性のあることが確認されたが, この特徴は, この属の種の解明に役立つものと思われる。 About three hundred specimens of fishes trawled in the Ross Sea have been identified. They represent twenty-four species and six families. Pleuragramma antarcticum BOULENGER is by far the commonest and Chionodraco myersi DEWITT and TYLER is the second in abundance. Two specimens of Vomeridens infuscipinnis (DEWITT) are included. This species has never been recorded from the Ross Sea. In Chionodraco myersi, variation in color and the relative length of the first dorsal fin seems to be related with the sexes. The collection contained nine specimens of the genus Cryodraco of which specific identification is difficult because of some confusion, evaluation of in the length of the lower lateral line and the relative length of the pelvic fin. departmental bulletin paper